Implementation of Improving Student Learning Outcomes with Innovative Learning Methods and Parenting During the Covid-19 Pandemic - Alim Perangin-angin; Fransiskus Gultom; Rameyanti Tampubolon; Lukman Pardede (Postgraduate, University of Mataram, 2022)
This study aims to improve the activeness and learning outcomes of chemistry students. Can be useful in providing an interesting learning experience and not boring students, through google classroom learning and parental parenting, students are directly involved in learning activities, to increase the activeness of student chemistry learning during the Covid-19 pandemic. This research is class action research (known with PTK) consisting of 2 cycles, where each cycle consists of four activities, namely: planning, action, observation, and reflection. Learning activities with the google classroom learning model and parenting will continue to the next cycle if success indicators have not been achieved. The sample in this study was class X MIPA students of Jambi Medan Private High School as many as 35 students. The results of the study using the google classroom learning model and parenting patterns during the Covid-19 pandemic. From the results of the research and discussion that have been obtained, several conclusions can be drawn, including In the first cycle, the number of students in the active category was 42.86% and the very active ones were 8.57% so the number of student activities was obtained by 51.43%; In cycle II, there was an increase in the activeness category by 34.29% and very active students experienced an increase of 57.14%, so that the number of student activities was obtained by 91.43%; and student learning outcomes have increased with the achievement of minimum completeness criteria (known with KKM) scores in cycle I of 62% and in cycle II obtained by 84.5%. So the number of student learning completion was obtained by 85.83%.